AF-equivalence relations - Molberg, Mats (MATHEMATICA SCANDINAVICA, 2006)
Let $R=\lim\limits_{\longrightarrow}R_{n}$ be the inductive limit of an ascending sequence of étale finite equivalence relations $R_n$ on the zero-dimensional space $X$. We prove that $R$ is an AF-equivalence relation.